2020
DOI: 10.3390/microorganisms8111715
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Probiotics on the Firmicutes/Bacteroidetes Ratio in the Treatment of Obesity and Inflammatory Bowel disease

Abstract: The two most important bacterial phyla in the gastrointestinal tract, Firmicutes and Bacteroidetes, have gained much attention in recent years. The Firmicutes/Bacteroidetes (F/B) ratio is widely accepted to have an important influence in maintaining normal intestinal homeostasis. Increased or decreased F/B ratio is regarded as dysbiosis, whereby the former is usually observed with obesity, and the latter with inflammatory bowel disease (IBD). Probiotics as live microorganisms can confer health benefits to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
658
3
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,103 publications
(725 citation statements)
references
References 103 publications
47
658
3
17
Order By: Relevance
“…The diseased subjects in our study changed their diet from an omnivorous type to softer and/or fermented items composed of natural homemade yoghurt, boiled rice with lentils, and custard. Compared to the healthy subjects, the high abundance of Actinobacteria in the diseased subjects could be justified by their dietary interventions (especially intake of natural yoghurt) which is in line with the previous studies indicating the prevalence of Bifidobacterium in patients receiving yoghurt [60][61][62].…”
Section: Discussionsupporting
confidence: 88%
“…The diseased subjects in our study changed their diet from an omnivorous type to softer and/or fermented items composed of natural homemade yoghurt, boiled rice with lentils, and custard. Compared to the healthy subjects, the high abundance of Actinobacteria in the diseased subjects could be justified by their dietary interventions (especially intake of natural yoghurt) which is in line with the previous studies indicating the prevalence of Bifidobacterium in patients receiving yoghurt [60][61][62].…”
Section: Discussionsupporting
confidence: 88%
“…Gut microbiome of humans is mainly composed of two major phyla, Bacteroidetes , and Firmicutes . Some researchers considered the F/B ratio ( Firmicutes vs. Bacteroidetes ) crucial to human health, while some do not ( Turnbaugh et al, 2009 ; Zhang et al, 2016 ; Stojanov et al, 2020 ). Accumulating literature shows that intestinal microbiota plays a critical part in the development of various diseases, such as cardiovascular diseases, diabetes, obesity, neurological diseases, cancer, and gastrointestinal diseases ( Clemente et al, 2012 ; Lo Presti et al, 2019 ).…”
Section: Effect Of Pb On Intestinal Microbiotamentioning
confidence: 99%
“…In particular, the relative abundance of Firmicutes significantly increased, while Bacteroidetes exhibited the opposite trend, which indicated that the Pb exposure enhanced the abundant ratio of Firmicutes vs. Bacteroidetes (F/B) to a certain extent ( Wu et al, 2016 ). In some views, an abnormal abundant ratio of F/B is recognized as a vital biomarker of adiposity and lipid metabolic disorder ( Turnbaugh et al, 2009 ; Stojanov et al, 2020 ). Moreover, the authors also detected a total of six taxonomic genera change by early life Pb exposure, with three genera dropped ( Lactococcus , Enterorhabdus , and Caulobacterales ) and three raised ( Desulfovibrionaceae , Barnesiella , and Clostridium XIVb).…”
Section: Effect Of Pb On Intestinal Microbiotamentioning
confidence: 99%
“…In fact, studies have shown an increase in this ratio. Contradicting results have been published earlier, some showing a decrease in this ratio due to a decrease of Bacteroidetes in ASD [ 86 , 87 , 88 , 89 ] and others showing an increase [ 90 ]. In GID, Firmicutes, which is normally the most dominant phylum in the microbiota of healthy guts, was observed at significantly lower levels, leading to an observed decrease in the F/B ratio [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 68%